2016
DOI: 10.1007/s00056-016-0054-0
|View full text |Cite
|
Sign up to set email alerts
|

Post-treatment changes in permanent retention  

Abstract: OBJECTIVES While permanent retention is today the method of choice to stabilize orthodontic treatment outcomes, recent studies have increasingly reported posttreatment changes in tooth position during permanent retention. We conducted this study to analyze changes in the anterior mandible, whether the changes follow an underlying movement pattern, and, aiming for a preventive strategy, whether any risk factors could be identified comparing findings with the pretreatment situations. METH-ODS We included 30 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
1
14

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(69 citation statements)
references
References 29 publications
1
52
1
14
Order By: Relevance
“…Wird bei ausgeprägten Platzdefiziten eine forcierte Erweiterung des Zahnbogens angestrebt, kann dies ein Stabilitätsrisiko für die kieferorthopädische Behandlung darstellen [11]. So sollte -unter Abwägung der therapeutischen Ziele -bei einem Missverhältnis zwischen Zahn-und Kiefergröße eine Extraktionsmaßnahme aus Stabilitätsgründen in Erwägung gezogen werden.…”
Section: Maßnahmen Zur Rezidivprophylaxe In Der Behandlungsplanungunclassified
See 1 more Smart Citation
“…Wird bei ausgeprägten Platzdefiziten eine forcierte Erweiterung des Zahnbogens angestrebt, kann dies ein Stabilitätsrisiko für die kieferorthopädische Behandlung darstellen [11]. So sollte -unter Abwägung der therapeutischen Ziele -bei einem Missverhältnis zwischen Zahn-und Kiefergröße eine Extraktionsmaßnahme aus Stabilitätsgründen in Erwägung gezogen werden.…”
Section: Maßnahmen Zur Rezidivprophylaxe In Der Behandlungsplanungunclassified
“…Die genaue Ätiologie scheint hier noch nicht abschließend geklärt zu sein, jedoch wird als mögliche Ursache u. a. ein nicht passives Einbringen des Retainerdrahtes aufgeführt [30]. Eigene Daten konnten zeigen, dass Zahnbewegungen während einer festsitzenden Retention vermehrt auftraten, wenn vorweg therapeutisch eine Vergrößerung der interkaninen Distanz im Unterkiefer und eine ausgeprägte Reduktion des Overjets stattgefunden hatte [11]. In solchen Fällen wird es als empfehlenswert angesehen, den festsitzenden Retainer mit einer herausnehmbaren Apparatur zu kombinieren.…”
Section: Welche Retentionsmaßnahmen Können Getroffen Werden?unclassified
“…However, unexpected tooth movements despite intact bonded retainers may occur [ 11 , 15 – 24 ]. Some articles on this subject are however case reports or small case series; thus, information regarding the incidence of such side effects is rare and ranges between 1.1 and 43.3% of the patients [ 11 , 16 , 19 ]. In some questionnaire-based survey studies, unwanted side effects were reported by 56.7 to 100% of respondent orthodontists, however only a small number of patients were involved [ 4 , 5 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Different patterns of unwanted tooth movements have been described: torque differences between two adjacent incisors, opposite torque of canines, and increased buccal or lingual inclination of single canines [ 11 , 16 , 19 , 22 , 23 ]. These movements are classified as newly developed posttreatment malocclusion rather than relapse, because they show no similarities to the pretreatment malocclusion [ 11 , 16 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation